2017
DOI: 10.1007/s40858-017-0201-1
|View full text |Cite
|
Sign up to set email alerts
|

Notes on powdery mildews (Erysiphales) in Thailand V. Golovinomyces

Abstract: Records of Golovinomyces species new to Thailand are described on the hosts Ageratum conyzoides, Bidens pilosa, Dahlia pinnata, D. × hortensis, Helianthus annuus, Lactuca indica, Laggera crispata, Sonchus oleraceus (Asteraceae), Lygisma inflexum (Asclepiadaceae), Myosotis scopioides (Boraginaceae), Coccinia indica, Coccinia grandis (Cucurbitaceae), Vigna umbellata (Fabaceae), Torenia fournieri (Linderniaceae), Plantago major (Plantaginaceae) and Verbena × hybrida (Verbenaceae). The identifications of the parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…A BLAST search against the nucleotide sequence data at GenBank showed 100% similarity with G. ambrosiae (Rudbeckia laciniata AB077622) and G. spadiceus (Zinnia elegans AB769425) all belonging to the composite tribe Heliantheae and G. circumfusus (Eupatorium chinense AB000934) available in GenBank. Our results are in agreement with previous studies, which have shown that ITS sequence do not possess enough variation to differentiate these closely related species (Khodaparast 2016;Meeboon et al 2018).…”
supporting
confidence: 93%
“…A BLAST search against the nucleotide sequence data at GenBank showed 100% similarity with G. ambrosiae (Rudbeckia laciniata AB077622) and G. spadiceus (Zinnia elegans AB769425) all belonging to the composite tribe Heliantheae and G. circumfusus (Eupatorium chinense AB000934) available in GenBank. Our results are in agreement with previous studies, which have shown that ITS sequence do not possess enough variation to differentiate these closely related species (Khodaparast 2016;Meeboon et al 2018).…”
supporting
confidence: 93%
“…Golovinomyces is characterized by having chasmothecia with mycelioid appendages, several, mostly 2spored asci, an asexual morph with catenescent conidia that lack fibrosin bodies, and mostly nipple-shaped appressoria. Golovinomyces currently encompasses 57 species and 5 varieties [1,[8][9][10][11][12][13]. Erysiphe cichoracearum [14] included nearly all of the species that are now assigned to Golovinomyces.…”
Section: Introductionmentioning
confidence: 99%
“…The morphological differences used to differentiate the species include above all, much broader conidia and dimorphic germ tubes belonging to the longitubus pattern within the Euoidium type of conidial germination in G. ambrosiae than in G. spadiceus [1]. Additional research has found G. spadiceus to be extremely plurivorous, occurring on hosts of the Heliantheae and other tribes of Asteraceae, e.g., Aster and Chrysanthemum [19], Chrysogonum [28], as well hosts of various other plant families, including Abelmoschus (Malvaceae) [29], Crotalaria (Fabaceae) [13], Persicaria (Polygonaceae) [11,13,30], Solanum (Solanaceae) [13], and Verbena (Verbenaceae) [13]. The taxonomic interpretation of the inclusion of a sequence obtained from a Japanese collection of powdery mildew on Eupatorium chinense in lineage III [19] caused an additional problem and raised the question whether the name G. circumfusus, originally described from Europe on Eupatorium cannabinum, is included in this species complex.…”
Section: Introductionmentioning
confidence: 99%
“…Many powdery mildew species have recently been identified by using a combination of morphological examinations of the asexual morph and molecular analyses in Thailand (e.g. Takamatsu 2015, 2016;Meeboon et al 2017Meeboon et al , 2018Takamatsu 2016, 2017a, b, c, d). Previous studies revealed that the asexual morph of E. quercicola may occur on a wide range of woody plants including various tropical fruit trees (Baiswar et al 2015;Cardoso et al 2017;Cho et al 2018;Desprez-Loustau et al 2017;Fonseca et al 2019;Kirschner and Liu 2014;Limkaisang et al 2006Limkaisang et al , 2005Siahaan et al 2016;Takamatsu et al 2018;Tam 2017).…”
Section: Discussionmentioning
confidence: 99%